Cloning and expression analysis of abcb 1 gene in Rasbora sarawakensis - Zain Illyaaseen, bin Khairudin (Universiti Malaysia Sarawak (UNIMAS), 2015)
The ATP-binding Cassette (ABC) gene family constitutes one the most abundant gene families in encoding transport proteins. The genes in this family are highly conserved across a variety of species. This great degree of conservation indicates its important role in organisms, particularly in the transport of substances across the plasma membrane. Mutations in genes of this critical superfamily can cause a wide range of genetic conditions which can cause neurological malfunctions and altered drug response